DC self-heating effects modelling in SOI and bulk FinFETs. Issue 4 (April 2015) - González, B.; Roldán, J.B.; Iñiguez, B.; Lázaro, A.; Cerdeira, A.
Abstract DC thermal effects modelling for nanometric silicon-on-insulator (SOI) and bulk fin-shaped field-effect transistors (FinFETs) is presented. Among other features, the model incorporates self-heating effects (SHEs), velocity saturation and short-channel effects. SHEs are analysed in depth by means of thermal resistances, which are determined through an equivalent thermal circuit, accounting for the degraded thermal conductivity of the ultrathin films within the device. Once the thermal resistance for single-fin devices has been validated for different gate lengths and biases, comparing the modelled output characteristics and device temperatures with numerical simulations obtained using Sentaurus Device, the thermal model is extended by circuital analysis to multi-fin devices with multiple fingers.